CUSTOMER EXPERIENCE MANAGEMENT AND E-COMMERCE BRAND PERFORMANCE IN A DIGITAL ENVIRONMENT (UNIZIK Journal of Marketing, 2026)
This study examines the relationship between customer experience management (CEM) and ecommerce brand performance in a digital environment, with a focus on online shoppers in Abia State, Nigeria. The research adopted a survey design, using both primary and secondary data sources. Primary data were collected through a structured online questionnaire administered via Google Forms. The sample size was determined using the Taro Yamane formula, from a population of 1,651 respondents, yielding 267 valid responses from 322 distributed questionnaire. Data were analyzed using descriptive statistics and Ordinary Least Squares (OLS) regression at a 0.05 level of significance. Findings reveal that website usability, delivery speed and reliability, payment convenience, customer service responsiveness, and complaint handling all have significant positive relationships with e-commerce brand performance. Among these, complaint handling emerged as the strongest predictor, indicating the importance of post-purchase experience in shaping consumer perceptions and trust. The study concludes that customer experience management is a critical driver of e-commerce brand performance, particularly in emerging digital markets. It recommends that ecommerce firms strengthen complaint resolution systems, improve logistics efficiency, enhance payment security, and optimize customer service responsiveness to build trust, improve satisfaction, and sustain long-term customer loyalty.
Keywords: Customer experience management, e-commerce, brand performance, digital.